Application of climatological approach to determine the temperature of radiation fogs formation - O. M. Hrushevskyi; A. O. Yatsyshen (Український гідрометеорологічний журнал, 2022)
The effectiveness of a radiation fog forecast is determined by the accuracy of a forecast for two values – temperature of fog formation and minimum air temperature. The accuracy of the first measurement significantly depends on a degree of adaptability of a forecast method to specific factors affecting the formation of fogs – orthography, local circulations, seasons, time of day, temperature-humidity stratification in the boundary layer of the atmosphere, etc. Taking into account each of them in a specific point will dictate its characteristics, whereas use of non-adapted fog forecasting methods will reduce their effectiveness.